Oxovitisins: A New Class of Neutral Pyranone-anthocyanin Derivatives in Red Wines - Jingren R He (2010)
A new class of stable yellowish pigments with similar unique spectral features, displaying only a pronounced broad band around 370 nm in the UV-vis spectrum, was detected in an aged Port wine fraction obtained by a combination of chromatography on TSK Toyopearl HW-40(s) and Polyamide resins. These compounds were identified by liquid chromatography-diode array detector/electrospray ionization mass spectrometry (LC-DAD/ESI/MS) and shown to be direct oxidative derivatives of carboxy-pyranoanthocyanins (vitisins A) by synthesis experiments performed in a wine model solution. Their structures were fully characterized by MS and NMR spectroscopy ((1)H, gCOSY, gHSQC, and gHMBC) and found to correspond to alpha-pyranone-anthocyanins (lactone or pyran-2-one-anthocyanins). Their formation involves first the nucleophilic attack of water into the positively charged C-10 position of vitisins, followed by decarboxylation, oxidation, and dehydration steps, yielding a new and neutral pyranone structure. The occurrence of these novel pigments in aged wines points to a new pathway involving anthocyanin secondary products (vitisins A) as precursors of new pigments in subsequent stages of wine aging that may contribute to its color evolution.